إدارة المعرفة وعلاقتها بالإبداع الإداري لدى قادة المدارس بمكة المكرمة من وجهة نظر المعلمين - الذبيانى، محمد عبدالله صالح; شريف، شريف محمد محمد Sherif, Sherif Mohammed Mohammed (جامعة أسيوط - كلية التربية, 2018)
هدفت هذه الدراسة للكشف عن العلاقة بين درجة ممارسة عمليات إدارة المعرفة وعلاقتها بالإبداع الإداري لدى قادة المدارس بمحافظة مكة المكرمة من وجهة نظر المعلمين، تبعاً لمتغيرات الدراسة (سنوات الخبرة، المرحلة التعليمية، المؤهل العلمي)، واعتمد الباحث في دراسته المنهج الوصفي الارتباطي، وطبقت الدراسة على عينة عشوائية تطبيقية مكونة من (370) معلماً من معلمي المدارس بمحافظة مكة المكرمة، والبالغ عددهم ( 5198 ) معلماً خلال الفصل الدراسي الثاني من العام 1438 ه/ 1439 ه، وتم استخدام الاستبانة كأداة لجمع المعلومات والبيانات، وخلصت الدراسة مجموعة من النتائج منها: أن درجة ممارسة قادة المدارس بمحافظة مكة المكرمة لإدارة المعرفة من وجهة نظر المعلمين جاءت متوسطة بشكل عام وعلى جميع الأبعاد ككل، كما أظهرت نتائج الدراسة أن مستوى الإبداع الإداري لدى قادة المدارس بمحافظة مكة المكرمة من وجهة نظر المعلمين جاء متوسط بشكل عام وعلى جميع الأبعاد ككل، كما أظهرت نتائج الدراسة أن هناك علاقة بين درجة ممارسة إدارة المعرفة ومستوى الإبداع الإداري لدى قادة المدارس. كما أوصت الدراسة إلى ضرورة عقد ورش عمل وندوات لإنتاج معارف جديد، إضافة إلى تنمية مهارات قادة المدارس في استخدام الشبكة العنكبوتية في عملية تبادل المعرفة، وضرورة إدخال الإبداع الإداري وإدارة المعرفة في تقييم الأداء الوظيفي لقادة المدارس.
This study aimed at revealing the relationship between the degree of knowledge management processes and their relationship to administrative creativity among the school leaders in Makkah Governorate from the point of view of the teachers according to the study variables (years of experience, educational stage. In his study, the researcher adopted the descriptive correlative approach. The study was carried out on a random sample of 370 teachers from schools in Makkah Governorate, in which their numbers are(5198) during the secondary school year (1438 AH / 1439H).The questionnaire was used as a tool for collecting information and data. The study concluded a set of results, including: The degree of the practice of school leaders in the province of Mecca to manage knowledge from the point of view of teachers came in the middle in general and on all dimensions as a whole. The results of the study also showed that the level of administrative innovation among the school leaders in Makkah Governorate from the point of view of the teachers is generally moderate and on all dimensions as a whole. In addition, the results of the study showed that there is a relationship between the degree of knowledge management practice and the level of administrative creativity among school leaders. The study also recommended the need to hold workshops and seminars for the production of new knowledge, in addition to developing the skills of school leaders in using the Internet in the exchange of knowledge, and the need to introduce administrative innovation and knowledge management in evaluating the performance of school leaders.
Keywords: الإدارة المعرفية -- الإبداع الإدارى -- القادة التربوية -- الإدارة المدرسية -- مكة المكرمة